The Influence of Interior Design on a House - Azika Arshad; Deepti Pande Rana (International Journal of Electronics Automation, 2024)
Interior design plays an important role in creating the atmosphere, functionality, and beauty of living spaces. This research paper examines the multifaceted impact of interior design on buildings and examines the impact of interior design on occupants' wellbeing, quality of life and overall satisfaction with t heir living environment. This article synthesizes the current literature to examine various aspects of interior design, including spatial arrangement, color composition, furniture arrangement, lighting, and decoration, and their impact on the physical, mental, and emotional well-being of residents. The work also explores the relationship between interior design and functional aspects such as organization, storage and adaptation to the needs and desires of the occupants. It also explores how interior design choices reflect culture, society, and personal identity, contributing to the empowerment and personalization of the home. The paper also discusses the role of technology and sustainability in contemporary interior design and its impact on creating healthy and environmentally friendly living spaces. By synthesizing empirical evidence and a theoretical framework, this study aims to raise awareness of the importance of interior design in enhancing individual well-being in everyday environments. Finally, the results contribute to a deeper understanding of the complex interactions between interior design and the overall experience of living at home, which has import ant implications for homeowners, designers, and policy makers.
Keywords: Environment; and colors; house; interior design; space